Interaction of attention and acoustic factors in dichotic listening for fused words. Issue 4 (4th July 2017) - McCulloch, Katie; Lachner Bass, Natascha; Dial, Heather; Hiscock, Merrill; Jansen, Ben
ABSTRACT: Two dichotic listening experiments examined the degree to which the right-ear advantage (REA) for linguistic stimuli is altered by a "top-down" variable (i.e., directed attention) in conjunction with selected "bottom-up" (acoustic) variables. Halwes fused dichotic words were administered to 99 right-handed adults with instructions to attend to the left or right ear, or to divide attention equally. Stimuli in Experiment 1 were presented without noise or mixed with noise that was high-pass or low-pass filtered, or unfiltered. The stimuli themselves in Experiment 2 were high-pass or low-pass filtered, or unfiltered. The initial consonants of each dichotic pair were categorized according to voice onset time (VOT) and place of articulation (PoA). White noise extinguished both the REA and selective attention, and filtered noise nullified selective attention without extinguishing the REA. Frequency filtering of the words themselves did not alter performance. VOT effects were inconsistent across experiments but PoA analyses indicated that paired velar consonants (/k/ and /g/) yield a left-ear advantage and paradoxical selective-attention results. The findings show that ear asymmetry and the effectiveness of directed attention can be altered by bottom-up variables.